Patterned variation: The role of psychological dispositions in social and institutional evolution - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2021)
The new institutional economics has one of its roots in evolutionary thinking. The idea is that there is competition among organizational forms. Some forms spread faster than others and thereby displace and eventually destroy the less well adapted forms. In the end, the most 'efficient' organizational formation will survive, where 'efficiency' is a social analogue for biological fitness. The process is predominately envisaged as a process of what I am going to term 'blind evolution': a combination of random variation and selection. The idea of randomness is put into question. If evolution is is to be able to work successfully on complex organisms or organizations, it is necessary that variation occurs in a patterned fashion with systematically correlated changes. Once the importance of patterned variation is established, it must be asked where the patterns come from. It will be argued that, for the purpose of the social sciences, these patterns are generated by psychological regularities, both cognitive and emotional. Features of patterning are discussed.
urn:nbn:de:bvb:19-epub-76567-4
Keywords: B15; B25; B52; D02; D23; E14; 330; evolution; evodevo; evo-devo; variation; selection; institutional economics; social psychology; channeling by constraints; hitchhiking; radiation; founder effects; irreversibly; functional shifts; evolutionary detours; punctuation